Critiques and convergences with Dependen cy Theory - Katz, Claudio (2018)
In the 1970s, Agustin Cueva was the main Marxist critic of Dependency Theories. He objected the thesis of associated development, questioned the metropolis-satellite vision and maintained intense controversy with Bambirra, Dos Santos and Marini; however, provided certain political confluences, in the following decade he participated in a theoretical meeting that modified the approach of underdevelopment. Cueva’s criticism helped reformulate the Marxist theory of dependency. He questioned early-on Cardoso’s non-subject functionalism and Frank’s mechanicalexogenism. He objected to pan-capitalist historical reasoning and attributed underdevelopment to the pre-eminence of large agrarian property. Pushed in controversies with regional singularism, he rejected the existence of specific laws of dependent capitalism. He developed intuitions on traditional endogenism without sharing its conclusions. He took an opposite view of Marini from what happened in Chile with Allende, but he converged in the debates with post-Marxism and neo-Gramscians. The success of Cueva is verified in the contrast with the trajectoryfollowed by the Theory of Regulation. In his maturity he suggested a theoretical synthesis that clarifies the distinction between underdevelopment, periphery and dependence. This union overcomes false counter-positions and resolves the theoretical status of dependency with the idea of paradigm. It also illustrates the loss of usefulness of endogensim versus the total primacy of capitalist structures.